HUBUNGAN KETERAMPILAN GERAK TERHADAP KEMAMPUAN DRIBBLING SEPAKBOLA PADA SISWA SSB U-13 RUMBAI PRATAMA PEKANBARU RIAU - Tanjung, Aswar Maulid; Juita, Ardiah; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research is correlational research. The research was conducted at SSB Rumbai Pratama in Pekanbaru City and took a population of all SSB students, then the sample in this research was a total sampling of 18 students. Data collection uses product moment correlation analysis techniques. The results of the research after the analysis were carried out were that there was a correlation value of r-count = -0.305 and the data showed that there was no correlation or a very low relationship. Obtaining these results shows that the hypothesis is not accepted, namely that there is no relationship between movement skills and soccer dribbling ability in SSB U-13 students at Rumbai Pratama, Pekanbaru, Riau. Based on this statement, it can be seen that overall in this study, movement skills and dribbling ability prove that the x variable is not an important or main variable in this study.Key words: Relationship between movement skills, dribbling, football